2012
DOI: 10.1523/jneurosci.5345-11.2012
|View full text |Cite
|
Sign up to set email alerts
|

δ-Opioid Receptor Function in the Dorsal Striatum Plays a Role in High Levels of Ethanol Consumption in Rats

Abstract: Binge-like patterns of excessive drinking during young adulthood increase the propensity for alcohol use disorders (AUDs) later in adult life; however, the mechanisms that drive this are not completely understood. Previous studies showed that the ␦-opioid peptide receptor (DOP-R) is dynamically regulated by exposure to ethanol and that the DOP-R plays a role in ethanol-mediated behaviors. The aim of this study was to determine the role of the DOP-R in high ethanol consumption from young adulthood through to la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 85 publications
3
35
0
Order By: Relevance
“…Taking the DOR-mediated depression of FSI-MSN synapses in the DLS following acute EtOH exposure together with the reported increase in GABA transmission onto DMS MSNs, EtOH appears to shape the global output of the striatum by modulating GABA synapses. Indeed, the importance of the presently described mechanism in drinking is supported by the findings of Nielsen et al (2012) that show striatal DOR blockade decreases repeated EtOH intake in rats, while activating striatal DOR increases consumption. In light of this, additional studies are necessary to understand the effects of EtOH on DOR-mediated depression of the FSI-MSN synapse in the DLS following a chronic drinking paradigm.…”
Section: Discussionmentioning
confidence: 83%
“…Taking the DOR-mediated depression of FSI-MSN synapses in the DLS following acute EtOH exposure together with the reported increase in GABA transmission onto DMS MSNs, EtOH appears to shape the global output of the striatum by modulating GABA synapses. Indeed, the importance of the presently described mechanism in drinking is supported by the findings of Nielsen et al (2012) that show striatal DOR blockade decreases repeated EtOH intake in rats, while activating striatal DOR increases consumption. In light of this, additional studies are necessary to understand the effects of EtOH on DOR-mediated depression of the FSI-MSN synapse in the DLS following a chronic drinking paradigm.…”
Section: Discussionmentioning
confidence: 83%
“…Considered alongside evidence that consumption of highly palatable food causes a surge of enkephalin in the DMS and that infusion of DAMGO into the DMS stimulates such consumption 34 , these findings point to an important role for enkephalin action at MOPrs in striatal function. Of course, enkephalins also act on DOPrs 22 , and behaviors such as ethanol consumption are known to be regulated by DOPrs in the dorsal striatum 35 . Furthermore, our findings identify a role for KOPrs in the dorsal striatum, whereas no clear KOPr- mediated synaptic effects have previously been observed.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, Carnicella, Amamoto, and colleagues (2009) showed that about one-third of the total ethanol amount consumed throughout the 24-h session is consumed within the first 30 min, generating a BEC of > 80 mg%, which meets the criteria of the National Institute on Alcohol Abuse and Alcoholism (NIAAA) for binge drinking in humans (National Institute on Alcohol Abuse and Alcoholism, 2004). Thus, this procedure is also used to model binge-like alcohol drinking in rats (Ahmadiantehrani et al, 2013; Barak, Ahmadiantehrani, et al, 2011; Ben Hamida et al, 2012; Carnicella, Amamoto, et al, 2009; George et al, 2012; Neasta, Ben Hamida, Yowell, Carnicella, & Ron, 2010, 2011; Nielsen et al, 2012; Simms, Nielsen, Li, & Bartlett, 2013). Moreover, in procedures that start the session in the light cycle, rats seem to consume lower levels of ethanol for several hours after the first 30 min of binge-like drinking (possibly until the dark cycle begins), and then consume high levels during the dark cycle (Barak, Ahmadiantehrani, et al, 2011; Carnicella, Amamoto, et al, 2009).…”
Section: Intermittent Access To 20% Alcohol In 2-bottle Choicementioning
confidence: 99%